A travessia da teoria da tendência antissocial à prática: uma contribuição psicanalítica - Roxo Junior, Hélio Antonio Anthero (2024)
This research aims to understand the theory of antisocial tendency and to develop a handling proposal for socio-educational care centres. With an important emphasis on the relationship between the mother (environment) and her baby, Winnicott constructed a complex theory on emotional development and antisocial tendency. His vision of psychopathology refers to environmental failures in the phases in which the subject has not yet acquired the capacity to deal with them. Adaptation failures are defined as traumas and can manifest themselves through various dynamics, including antisocial tendencies. In this work, we use Winnicott's main references to understand the type of trauma associated with antisocial tendency and how the author developed his theory. By analysing experiences in the care of young offenders, we seek to bring Winnicott's constructions closer to the Brazilian context and propose a model of environmental adaptation in care institutions capable of building a potential space for creativity and healing.